Custom and its interpretation in international investment law. edited by Panos Merkouris, Andreas Kulick, José Manuel Álvarez-Zarate, Maciej Żenkiewicz. - Merkouris, Panos; Kulick, Andreas, 1982-; Alvarez Zárate, José Manuel; Żenkiewicz, Maciej, 1984- (Rules of interpretation of customary international law.., 2024)
At first glance, one may think of international investment law as a response to custom (or lack thereof), instead of a field of its application. However, in fact, the opposite is the case. The interpretation and application of customary rules and principles are the bread and butter of international investment law and arbitration. With a diverse range of expert contributors, this collection traces how customary international law is practised in international investment law. It considers how custom should be interpreted and how its rules and principles should be understood and applied by investor-state arbitral tribunals. Raising and addressing vital questions surrounding custom and international law, this collection is a necessary contribution to the scholarship of the theory and history of customary international law and international investment law. This title is also available as Open Access on Cambridge Core.